An assessment of the South African law governing breach of contract : a consideration of the relationship between the classification of breach and the resultant remedies - Venter, Cindy Michelle (Stellenbosch : Stellenbosch University, 2012)
Thesis (LLM)--University of Stellenbosch, 2005.